Application of Daily Prayers Using Three Languages ​​(Arabic, Malay, English) for Children: Penerapan Doa Sehari-hari Menggunakan tiga Bahasa (Arab, Melayu, Inggris) pada Anak - Rambe, Sari Kiswah; Mavianti, Mavianti (Universitas Muhammadiyah Sidoarjo, 2022)
Prayer is a means of worship to invoke Allah SWT and ask for help no matter what is happening on this earth. Prayer is a sign that people really need Allah every breath because Allah His SWT can easily change things according to His will. Language is the means of communication that humans have acquired from birth. A child's language proficiency begins with mastering a first language, often called the mother tongue. The purpose of this study was to determine children's verbal intelligence, specifically Malay, Arabic, and English used as observation objects. Data collection techniques used for observational and interview data. The results of this study demonstrate that making daily prayer a habit in a school environment can apply children's linguistic intelligence, especially Malay, Arabic, and English, during early childhood.